Pass-band reconfigurable spoof surface plasmon polaritons. (9th March 2018) - Zhang, Hao Chi; He, Pei Hang; Gao, Xinxin; Tang, Wen Xuan; Cui, Tie Jun
Abstract: In this paper, we introduce a new scheme to construct the band-pass tunable filter based on the band-pass reconfigurable spoof surface plasmon polaritons (SPPs), whose cut-off frequencies at both sides of the passband can be tuned through changing the direct current (DC) bias of varactors. Compared to traditional technology (e.g. microstrip filters), the spoof SPP structure can provide more tight field confinement and more significant field enhancement, which is extremely valuable for many system applications. In order to achieve this scheme, we proposed a specially designed SPP filter integrated with varactors and DC bias feeding structure to support the spoof SPP passband reconfiguration. Furthermore, the full-wave simulated result verifies the outstanding performance on both efficiency and reconfiguration, which has the potential to be widely used in advanced intelligent systems.